Imagination and environmental political thought the aftermath of Thoreau - Bowman, Joshua J. (Politics, literature, and film, 2018)
"This book explores and evaluates Henry David Thoreau's political thought through the lens of a theory of imagination and considers his legacy for later environmental thought. This book will interest anyone curious about Thoreau's relationship to environmentalism and the intersection of environmental humanities and politics"--